TINJAUAN KERUANGAN DAN PEMETAAN KAWASAN KONVERSI LAHAN PERTANIAN TAHUN 2000-2009 DI KABUPATEN MAGELANG - , SUSETYO ADI WIBOWO, Dr. Ir. Benito Heru Purwanto, M.Agr. MP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Agricultural land conversion is the change from the original form of agricultural to non-agricultural land use. Land conversion is a logical consequence of the increase in activity and population and other development processes. Magelang Regency is an area that still has a lot of productive agricultural land. Lately agricultural land area in the Magelang regency is decreasing. This study was conducted during May to September 2013. The 2000 and 2009 land use map overlaying process was conducted to determine the conversion of agricultural land in the Magelang Regency. The results showed that the conversion of agricultural land based on its use in Magelang Regency in 2000 to 2009 covering an area of 6,521 ha consist of the gardens of 1,457 ha, 2,905 ha of Irrigation Rice, Rainfed Rice of 1886 ha, dryland of 272 ha which then becoming the central area of economic activity, education, industry, cullinary area, lodging and services predominantly residential areas. Regional growth patterns and conversion of agricultural land in the Magelang Regency combination the Leap frog and Ribbon pattern contained in the strategic development and good accessibility along arterial roads namely Magelang - Yogyakarta - Semarang as well as the collector roads. The main factors that dominantly cause the conversion of agricultural land in the Magelang Regency, namely population growth and agricultural land use conversion into the greater area revenue.